Aplikasi Teknologi Budidaya Kelengkeng Super Sleman di Padukuhan Gejayan - DARYONO, BUDI SETIADI; RABBANI, ANNAS; PURNOMO, PURNOMO (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2016)
Longan (Dimocarpus longan L.) is not an indigenous fruit from Indonesia. Thus, the demands for this fruit were supplied by importing them from nearby countries such as Vietnam, Thailand, and China. Longan has been cultivated and developed in Indonesia in order to supply the local needs and to reduce the rapid flows of importing Longan. Recently, a brand new breed of local Longan has been engineered from Sleman District of D.I.Yogyakarta Province, known as Kelengkeng Super Sleman (KSS). The KSS well adapted to medium-high above sea level- terrain, the most typical terrain in Sleman. Some prosperous features of this Longan cultivar were had a short harvesting time (2 years), thicky flesh, low water content, and able to be induced twice per year for flowering (to produce fruits). All of this goodness thus been introduced to rural communities of Padukuhan Gejayan, Desa Condongcatur, Depok, Sleman, D.I.Yogyakarta by a well designed community service programme. The kind of activites that was going on in this programme were workshop, training, and assistance. Workshop was emphasized on the prospectous consequences of planting Longan trees (KSS) for a long term until could be developed into local industrial product (One Village One Product/OVOP concept), basic knowledge on Longan diversity, KSS cultivation technology, basic knowledge on plant physiology, environmental development based on Education for Sustainable Development (EfSD), and potential local market for KSS. Training was mainly focused on KSS seedling production by both apical stem grafting method and medium preparation method, KSS plantation in some villager houses for a pilot project on how to maintain KSS such as health evaluation, health recovery for infested or unhealthy plant, method on lateral branching development, method on hormone-induced flowering, and application of resting period for after-harvesting plant. Assistance has been actively conducted during training to motivates villager to be get involved. Some positive indicators for implementation of this programme are both the great enthusiasm on KSS Longan plantation in communities and “the shifting paradigm” on KSS Longan maintenance for which has been long considered to be both impractical and arduous.